Of lads and ear'oles: School, work, and the microsociology of social reproduction. (December 2018) - Voyer, Andrea
This article draws on structural symbolic interactionism (SSI) to extend Willis's insights into social reproduction and social mobility. Willis contrasts the lads with the ear'oles – working-class youth who conform to the requirements and ideology of school. If, as Willis argues, working-class youth encounter conflict between the culture of school and the culture of labour, then the ear'oles' pro-school behaviours may be interpreted as rebellious in their own right. SSI suggests that the ear'oles' continued attachment to school requires abandoning or delaying adoption of the adult breadwinner role – a working-class role-identity assigned to those who finish required schooling, find jobs, and establish independence. While the lads conform to the behavioural norms and values of their class cultural milieu through their nonconformity at school, the ear'oles opt for school at considerable social cost. As successful ear'oles experience mobility, these class 'straddlers' struggle with feelings of inadequacy and guilt.